2008
DOI: 10.1007/s00330-008-0967-0
|View full text |Cite
|
Sign up to set email alerts
|

The Amplatzer vascular plug for large vessel occlusion in the endovascular management of aneurysms

Abstract: The Amplatzer vascular plug (AVP) is derived from the Amplatzer device used in correction of cardiac septal defects. We present a large series of the use of the AVP in the endovascular management of aneurysms. Three patients with a combination of aortic and peripheral aneurysms underwent embolisation with the AVP. Plugs with 10-16 mm diameter were used and delivered using introducer/guiding sheaths. A total of 16 internal iliac arteries, 2 common iliac arteries (CIA), 4 subclavian (SCA) arteries, 1 superior me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Rather than coils, we selected the Amplatzer Vascular Plug II, which has been used to occlude septal communications, fistulas, and hypogastric and subclavian arteries during endovascular repair of aortic aneurysms. [4][5][6][7][8][9][10][11][12][13][14] Although it may seem contradictory to use a custom-made device in a patient for whom it was not designed, experience has taught that there is room for a certain amount of variation in positioning when it comes to branched stentgrafts, since there are many anatomical similarities between the visceral arteries. 2,15 As Chuter's group 15 proposed recently, the device described here could probably soon serve as the basis for a ''standardized'' multi-branched TAAA stent-graft, eliminating the wait for a customized endograft to be made.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than coils, we selected the Amplatzer Vascular Plug II, which has been used to occlude septal communications, fistulas, and hypogastric and subclavian arteries during endovascular repair of aortic aneurysms. [4][5][6][7][8][9][10][11][12][13][14] Although it may seem contradictory to use a custom-made device in a patient for whom it was not designed, experience has taught that there is room for a certain amount of variation in positioning when it comes to branched stentgrafts, since there are many anatomical similarities between the visceral arteries. 2,15 As Chuter's group 15 proposed recently, the device described here could probably soon serve as the basis for a ''standardized'' multi-branched TAAA stent-graft, eliminating the wait for a customized endograft to be made.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, as detachable balloons have become unavailable in the US, the Amplatzer Vascular Plug has been reported as having potential utility in neurointerventional procedures. 3,4,8,[10][11][12][13] It provides a relatively costeffective way to occlude parent arteries or abnormal fistulous connections in cases in which a large number of coils might otherwise be required. One potential drawback of the Amplatzer Vascular Plug is the attendant risk of thromboemboli, as it may take up to 30 minutes to completely occlude blood flow, and its porous nature may allow for clots to escape from the plug.…”
Section: Discussionmentioning
confidence: 99%
“…New advanced occlusion devices have already been used as a therapeutic alternative to coil embolization in certain cases . For example, vascular plug has become an essential tool in a variety of clinical settings such as the treatment of arterio‐venous malformations, subclavian and internal iliac artery (IIA) occlusion in endovascular aneurysm repair (EVAR), and peripheral aneurysms where maintenance of vascular continuity is not a priority . It is reported that single occlusion device can occlude large arterial trunks, thus decreasing procedure length , the amount of contrast medium necessary, and the patient's radiation dose .…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that single occlusion device can occlude large arterial trunks, thus decreasing procedure length , the amount of contrast medium necessary, and the patient's radiation dose . In addition, the precise deployment of the new device and its effective anchor preclude frustrating incidences of distal embolization and malperfusion that are more common in coil deployment Despite these advantages, the use of a large introducer/guiding sheath may be a limiting factor in vascular plug use as it is not always feasible to position a sheath at the site of embolization in highly tortuous arteries . In addition, the relatively long occlusion time has been mentioned as a concern .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation